An Emirati Tapestry of Time: A narrative inquiry of the meaning and experience of time - Kenaid, Kaltham (2015)
This research investigates how time is experienced and what time means for the seven chosen Emirati participants. An interpretative, qualitative framework underpins this research project is guided by the philosophies of Hans-Georg Gadamer and Martin Heidegger. Using a narrative inquiry methodology, it weaves the simple narratives of the participants’ experiences including the temporal domains of past, present, and future. The collected data is derived from in-depth interviews informed by the three-interview series suggested by Irving Seidman (2006). The experiential data analysis is guided by Paul Ricoeur’s theory of interpretation. The analysis brings to light the narratives and descriptions for each participant’s time experience. The main thematic analysis of participants’ responses are organised into three main thematic categories. These themes are: time consciousness, social time, pedagogical time and future projections with a focus on pedagogical time. The study presents the participants’ narratives as thick descriptions of their experience and weaves their narratives into an Emirati Sadu (traditional Bedouin weaving). The findings indicate that the pedagogical time experience was influenced by the student’s moods of boredom and the teacher’s instructional methods. The teacher played a constructive role when she was attentive to the needs of the student. As for the external environment, the findings illustrate that the speed of life to which the participants were exposed created a detachment from a rich past instead of a continuation of such time experience. Implications for pedagogical leadership and practice are offered. Future research is also suggested using different methodologies to determine other aspects of Emirati time experience in the educational field.